Hybridization altered the gut microbiota of pigs - Wei, Limin; Zeng, Bo; Zhang, Siyuan; Guo, Wei; Li, Feng; Zhao, Jiangchao; Li, Ying (Frontiers in Microbiology, 2023)
Mammalian gut microbiota plays an important role in the host's nutrient metabolism, growth, and immune regulation. Hybridization can enable a progeny to acquire superior traits of the parents, resulting in the hybridization advantage. However, studies on the effects of hybridization on the pigs' gut microbiota are lacking. The gut microbial composition and diversity of domestic pigs (Duroc), wild boars (F0), hybrid second-generation wild boars (F2), and hybrid fourth-generation wild boars (F4) were analyzed using the 16S rRNA gene sequencing technology. The sequencing results revealed that the gut microbiota of F4 exhibited a host-like dominance phenomenon with a significant increase in the abundance of Lactobacillus and Bifidobacterium. The beta diversity of Duroc was significantly different from those of F0, F2, and F4; after the host hybridization, the similarity of the beta diversity in the progeny decreased with the decrease in the similarity of the F0 lineage. The gut microbiota functions of Duroc, F0, and F4 pigs were analyzed and compared using metagenomic technology. The results showed that the significantly enriched metabolic pathways in F4, such as environmental, circulatory system, fatty acid degradation adaptation, and fatty acid biosynthesis, were similar to those in F0. Moreover, it also exhibited similar significantly enriched metabolic pathways as those in Duroc, such as carbohydrate metabolism, starch and sucrose metabolism, starch-degrading CAZymes, lactosedegrading CAZymes, and various amino acid metabolism pathways. However, the alpha-amylase-related KOs, lipid metabolism, and galactose metabolism in F4 were significantly higher than those in Duroc and F0. Non-targeted metabolome technology analysis found that several metabolites, such as docosahexaenoic acid, arachidonic acid, and citric acid were significantly enriched in the F4 pigs as compared to those in F0.Based on Spearman correlation analysis, Lactobacillus and Bifidobacterium were significantly positively correlated with these metabolites. Finally, the combined metagenomic and metabolomic analysis suggested that the metabolic pathways, such as valine, leucine, and isoleucine biosynthesis and alanine aspartate and glutamate metabolism were significantly enriched in F4 pigs. In conclusion, the gut microbiota of F4 showed a similar host "dominance" phenomenon, which provided reference data for the genetics and evolution of microbiota and the theory of microbial-assisted breeding.